THE ROLE OF MANDATORY INSURANCE IN THE MODERN INSURANCE SYSTEM - Hamraeva, F.Sh. (International Journal of Psychosocial Rehabilitation, 2020)
The article describes the role of compulsory insurance in the domestic insurance market, the toric principles, its practice and problems, as well as practical recommendations for their solution.